Korelasi Antara Immature Granulocyte dan Delta He Sebagai Penanda Inflamasi Pada Penderita Dengan Lekositosis - Novina Aryanti; Juli Soemarsono (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2016)
Immature Granulocytes are considered as an inflammation marker. Recently Delta He is suspected to be a novel marker of inflammation. The aim of this study was to know the correlation of Immature Granulocytes and Delta He as inflammation marker in patients with lecocytosis. This research used whole blood-EDTA samples from 50 lecocytosis patients in the Dr. Soetomo Hospital Surabaya from 10 until 17 December, 2011 were studied Immature granulocytes and Delta He were examined by Flowcytometry (Sysmex XE 2000i). Analysis of the results was performed by Pearson product moment. Mean result of Immature Granulocytes and Delta He from 50 patients with lecocytosis was 0.37 x 103/µL and 3.03 pg. According to Pearson analysis test there was a correlation between Immature Granulocytes and Delta He (r = 0.26), but this was not significant (p > 0.05). Inflammation induced cytokine release and rise hepcidin, the result was decrement of ferroportin from duodenum and macrophage so the iron supply to erythropoetic precursor decrease, and the hemoglobin synthesis (Ret He) decrease. The rise of Immature Granulocytes were not happened in all lecocytosis patients, it were not certain suffered sepsis. There was no significant correlation between Immature Granulocytes and Delta He in patients with lecocytosis. A further research with more samples to determine that Delta He can be used as an inflammation marker is needed